2007
DOI: 10.1093/humrep/dem084
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-guided myometrial biopsy in the definite diagnosis of diffuse adenomyosis

Abstract: Laparoscopy-guided myometrial biopsy is a valuable tool for obtaining a definite diagnosis of diffuse adenomyosis with preservation of the uterus in infertility workup or in the evaluation of dysmenorrhea or chronic pelvic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…All were prospective studies and included histopathology results on uterine specimens from women undergoing hysterectomy for benign conditions as reference standards. However, the method of taking a biopsy was different in each (laparoscopic guided, Brosens et al, 1995); laparoscopic and ultrasound guided (Jeng et al, 2007) and on hysterectomy specimens (Vercellini et al, 1998)]. The actual number of biopsies per patient varied from 1 to 10 (1 by Vercellini et al, 1998 and10 by Brosens et al, 1995) although all used a 14-gauge needle.…”
Section: Biopsymentioning
confidence: 99%
“…All were prospective studies and included histopathology results on uterine specimens from women undergoing hysterectomy for benign conditions as reference standards. However, the method of taking a biopsy was different in each (laparoscopic guided, Brosens et al, 1995); laparoscopic and ultrasound guided (Jeng et al, 2007) and on hysterectomy specimens (Vercellini et al, 1998)]. The actual number of biopsies per patient varied from 1 to 10 (1 by Vercellini et al, 1998 and10 by Brosens et al, 1995) although all used a 14-gauge needle.…”
Section: Biopsymentioning
confidence: 99%
“…In 1997 a true-cut transhysteroscopic device was developed to obtain basal endometrium and JZ biopsies (33), and in 2003 a TVU-guided biopsy of the uterus was introduced (34); a study involving 100 patients with symptoms suggestive of adenomyosis reported 98% sensitivity, 100% specificity, and 100% positive and 80% negative predictive value for laparoscopy-guided myometrial biopsies (35).…”
Section: Progress In Diagnosismentioning
confidence: 99%
“…A uterine manipulator with die injection system was inserted into the cervix under direct vision at beginning of the surgical procedure and used to drive the methylene blue solution into the uterine cavity to verify tubal permeability. Laparoscopic uterine biopsy was performed where the dye reached the uterine external layer (Fig 1) to confirm the presence of adenomyosis [23] in cases where the preoperative evaluation (ultrasound and MRI) did not suggested adenomyosis.…”
Section: Methodsmentioning
confidence: 99%